If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18x + -25 = 7 Reorder the terms: -25 + -18x = 7 Solving -25 + -18x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + -18x = 7 + 25 Combine like terms: -25 + 25 = 0 0 + -18x = 7 + 25 -18x = 7 + 25 Combine like terms: 7 + 25 = 32 -18x = 32 Divide each side by '-18'. x = -1.777777778 Simplifying x = -1.777777778
| .75(n+6)-.5(n-3)=0 | | 4(t-9)=14-t | | x-a/l=x-b/m | | 7r+17=4R-24 | | 6x-7=2x+49 | | 5x+76+3=180 | | (6x-3)+x+(3x-3)=p | | 2x+15=4x | | 8=kover-3-2 | | 0.07(3t-5)=0.21(t+4)-1.19 | | (2)13.5-3=24 | | 4x=-8x+24 | | 0.4x+0.9=0.7x-0.6 | | 6(x+2)-2=3x+3(5+x) | | m=-5(4-m)+2 | | y^-8/y^5 | | 4x+5y-5=-6x+5y-3 | | 7+n=23 | | A/8=0 | | 2(X+1)-3x=3(3x+2x) | | 40=2x+64 | | 1(-5y+-10)=10 | | F(3)=7x-2 | | -8x+25=13 | | 3x-40=7x+20 | | -96=69-6-2x | | y=8+2x^2-x^4 | | -104=-4(-4k-2) | | 6d+8d+7d-4= | | -104=-(-4k-2) | | -104=-4(4k-2) | | 7x-112=2x-7 |